Patrimônio histórico arquitetônico e urbanístico de Diamantina-MG: paisagem e lugar pela vivência dos insiders - Rahyan de Carvalho Alves (2021)
Diamantina's heritage “landscape and place through the experience of insiders” will be our field of analysis based on the categories already mentioned and through discussions involving the themes of memory, heritage and legitimacy, coupled with the universe of the development of investigations and geographical practices. The empirical basis of the research will take place in a vertical and deep way in the emblematic city of Diamantina (located in the Jequitinhonha Valley - Minas Gerais). It should be noted that we start from the assumption that this city is home to an architectural and urban heritage set, of enormous relevance and uniqueness, listed by IPHAN and UNESCO, characterizing there the exceptionality of the Place and its landscapes, a place where an important chapter of the biography of urbanization and the economy of Brazil was developed, whose houses, streets, alleys, squares, churches, among other architectural icons were consecrated, as symbols of the history of a nation and its people. Based on this premise, we seek to answer the following questions: “the legal act that made the city of Diamantina a World Heritage Site and the use of its heritage is currently perceived as legitimate, in terms of its historical-geographic representativeness and as an experience of living for your people?. In this perspective, the general objective of the thesis is precisely to seek to analyze the legitimacy of the historical architectural and urban heritage set of Diamantina, considering the use and experience of a world heritage according to the perception of Diamantina residents. To answer these questions, we resorted to different methodological contributions, choosing as research procedures: conducting interviews (semi-structured and narrative), transversal walk and bibliographic and documentary research. We perceive the methodological path, pertinent and adequate for this, in terms of the nature, essentially qualitative and humanistic of the research, in which we will have the opportunity to register in the light of the conceptual categories of analysis and paradigms of the interpretation of Cultural Geography, Geography of Representations. In the research process, we seek to find a “perception unit” that can demonstrate the subjects' relationships with/the place/places and the ways of feeling and perceiving the landscape and heritage, to the point of becoming clear, if exists, a place-memory-heritage relationship. Furthermore, we will reflect on the following question: from this process, a patrimonialism emerges, which can affirm or deny the construction and institutional maintenance of heritage. We noticed that most of the interviewees emphasize that they recognize the historical and geographical importance of the heritage complex, in addition to its legal and sociocultural use, and emphasize that they would maintain the structure of the heritage properties. It was still possible to detect that there are tensions about the valuation of the heritage for those who live in the central region and those who live in marginal areas of the city. However, it is necessary, in parallel to the work already carried out by the public authorities (such as the Heritage Education Program), to give notoriety and a turn to the residents of the districts located far from the colonial historic center, emphasizing the understanding that the cultural heritage of a people comprises the works of its artists and their will, giving meaning (legal and legitimate) and use to the assets for all.